Lalaki Dao, babae Sha meteor garden and its gender(ed) representations in retrospect - Sales, Marlon James S. (2004)
This paper, which is based on the author's undergraduate thesis on translation as a means of cultural appropriation, is a critique of the Taiwanese soap opera Meteor Garden (MG). It presents the various gender(ed) archetypes for both male and female characters employed in the serialized drama. Although the chinovela seems to be an innovation from its forerunners in Philippine media, the Hispanic American soaps, the traditional representations of gender found in said soaps are also evident in the text of MG. The paper also discusses audience interpretations of gender representations in MG These interpretations are the result of a translation exercise that required the adolescent viewers to provide their own Filipino translations of selected MG scenes in their original Chinese version with English subtitles. Although MG has a tendency to romanticize gender(ed) relations, its audiences remain enthusiastic viewers possibly because the soap enacts their dreams in ways that are understandable and uncomplicated.
Includes bibliographical references (pages 69-72).